EDUKASI PERTOLONGAN PERTAMA GAWAT DARURAT (PPGD) SEBAGAI PENGUAT KETERAMPILAN PADA SISWA SMK - Silfiana Nisa Permatasari; Kinanti Ayu Puji Lestari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
An emergency is an event that occurs suddenly, resulting in a person requiring immediate and appropriate treatment and assistance. Everyone needs first aid knowledge and skills. Emergency First Aid (PPGD) requires assistance and initial treatment that can be carried out by ordinary people, including students of SMK Pharmacy Kapasari Surabaya. The target of this activity is class XII SMK students consisting of 29 students. The purpose of organizing this educational activity is to strengthen skills so that participants receive provisions that can be applied to the community. This counseling will be held on May 18, 2022, located at Graha Ilmu, Jl. Intermediate Potato No. 81. Service activities use simulation and role play methods as well as discussions to increase knowledge about the material. Community service activities produce changes that are in accordance with the output targets, namely increasing students' knowledge, attitudes, and skills about First Aid with CPR (Cardiopulmonary Resuscitation) or Basic Life Support, fractures, burns, choking and electric shock.